The application of virtual bio-modelling for optimization of surgical treatment of the patients with traumatic injuries of the orbits. - Rahimov, Ch.; Farzaliyev, I.; Ahmedov, S. (Actual Dentistry, 2018)
Abstract. In cases of traumatic injuries of one or several wall of the orbit, beside esthetic disturbances one could face with functional derangements such as diplopia and enophthalmia, what has high impact on quality of life of the patient. The aim of current study was to improve the outcomes of surgical treatment of such pathologies base on algorithm of application of bio modeling in preoperative planning. Clinical study was performed on 77 patients with injuries of the orbital walls, which was divided into 2 groups based on different approaches in preoperative preparations: main group – the application of bio modeling and control group – the application of traditional methods of preoperative planning. The method of bio modeling allows to perform detailed analysis of injured region, create virtual template of orbital plate, determine its relation to different bones of facial skeleton, transfer the shape of virtual plate to real one, bend the real plate according to healthy site, and exclude the necessity to print plastic models for preoperative implants adaptation. The transformation of virtual measurements allowed installing orbital implant in defect region without additional navigation devices. Developed algorithm is much simple and cost effective comparative to traditional methods of preoperative planning of surgical reconstruction of defects and deformities of the orbital walls, improves the functional and esthetic outcomes of the treatment, and significantly decrease the duration of treatment. Key words: traumatic injuries of orbit, virtual preoperative planning, titanium orbital implants, diplopia.